2005
DOI: 10.1017/s0031182005009029
|View full text |Cite
|
Sign up to set email alerts
|

Variation among faecal egg counts following natural nematode infection in Scottish Blackface lambs

Abstract: Faecal egg counts were examined in 2 flocks of naturally infected Scottish Blackface sheep in southern and central Scotland. The distribution of mean counts was right skewed and similar to a gamma distribution. The counts varied with month, with mean counts rising from May to July, then falling but rising again in October, although data within each year did not always show such a clear pattern. There was no significant difference in mean egg count between the 2 farms examined. The distribution of egg count var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…The ultimate aim of the project is to enable the selection of lambs resistant to T. circumcincta. The current criteria for selection are a number of indicator traits, primarily FEC (Davies et al, 2005;Gill, 1991;Stear et al, 2006a) and pathological parameters, including eosinophilia (Stear et al, 2002) and IgA antibody levels (Davies et al, 2006;Stear et al, 1997;Strain et al, 2002). However, such phenotypic markers are quite difficult to establish as it necessitates challenge infection with the parasite.…”
Section: Discussionmentioning
confidence: 99%
“…The ultimate aim of the project is to enable the selection of lambs resistant to T. circumcincta. The current criteria for selection are a number of indicator traits, primarily FEC (Davies et al, 2005;Gill, 1991;Stear et al, 2006a) and pathological parameters, including eosinophilia (Stear et al, 2002) and IgA antibody levels (Davies et al, 2006;Stear et al, 1997;Strain et al, 2002). However, such phenotypic markers are quite difficult to establish as it necessitates challenge infection with the parasite.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these findings were only based on abomasum counts, excluding the abundant T. vitrinus in the small intestine. Stear et al (2006) found that in Blackface lambs naturally infected with a mixture of nematode species of which T. circumcincta predominated, individuals with high mean strongyle egg counts did not necessarily have a greater number of adults but had a greater number of species other than T. circumcincta, particularly T. axei and T. vitrinus. These findings and those of previous studies (Bishop and Stear, 2000) suggest that T. circumcincta is prone to density-dependent constraints on fecundity and hence strongyle egg count is not as reliable an indicator of T. circumcincta burden as it perhaps is for other contributing species.…”
Section: Implications For Strongyle Egg Count As a Measure Of Speciesmentioning
confidence: 91%
“…Resistance is defined as the ability of a host to initiate and maintain responses to suppress the establishment of parasites and /or eliminate the parasite load (Woolaston and Baker, 1996). Breeding for resistance utilizes sheep genetic variation to select for resistant to nematode parasites, and has been the subject of many reviews covering related work (Albers and Gray, 1987;Woolaston and Baker, 1996;Stear et al, 1997;Stear et al, 2006;Davies et al, 2006). Selection for resistance has traditionally been based on quantitative measurements of phenotypic traits.…”
Section: Breeding For Resistance To Gastrointestinal Nematodesmentioning
confidence: 99%